An experimental study and axial tensile constitutive model of the toughness of PP-SACC for rapid repairs - Xie, Wen; Xu, Xuefeng; Xu, Chunlei; Tian, Feng; Mao, Qiwen; Li, Helong; Liu, Lin; Qin, Gongyi (Frontiers in Built Environment, 2023)
To improve the economic benefits of ECC and control the repair cycle, the repair materials were designed with polypropylene (PP) fiber featuring low cost and the sulfoaluminate cement featuring fast setting employed as the key components of the mixture. The effects of water-binder ratio, fiber content, and aggregate size on the flowability, mechanical properties, and toughness of the Polypropylene fiber reinforced Sulfoaluminate cementitious composite (PP-SACC) were explored in this paper. Based on the experimental measured axial tensile stress-strain curves, the constitutive model of PP-SACC was derived in terms of the fiber content and the water-binder ratio. Simultaneously, the correlation coefficients of the mixture indexes on the tensile properties were explored based on the revised grey relational analysis. Test results indicated that the fiber content and the water-binder ratio were the most important factor that affects the mechanical properties, the toughness, and the fluidity. However, the influences of aggregate size were slight. PP-SACC mixture with an aggregate size of 75 𝜇m, a water-binder ratio of 0.30, and a fiber content of 3.0 % generated an excellent toughness and exhibited the flexural hardening phenomenon under bending load.